Qualidade no serviço de transporte público por ônibus: proposta de uma escala de mensuração sob a ótica dos usuários - Lima, Diego Gomes de (2018)
The theme of the quality of public services with a focus on the public transport service by buses demonstrates relevance, considering the increase in the number of cars on the roads, in addition to traffic jams, delays and increasing pollutant indices. In this way, improving the quality of public transport contributes to minimize these effects and attracting new users to the service, being essential to evaluate the quality offered and to involve users in this process. Therefore, the objective of this research is to analyze the variables that influence the perception of quality of public transportation by bus and the satisfaction of users with the service. Through a systematic review of the literature it was verified that the construct quality of public transport by bus has multidimensional nature, composed by several variables that allow its evaluation. For this, an instrument was developed to measure the construct through a model with eight steps necessary for its validation. Next, we analyze the relation between quality dimensions and satisfaction with services through a multiple linear regression model. As a research strategy, the survey was adopted through the quantitative approach. The sample was applied with 834 respondents, users of public transport services in the cities of João Pessoa and Campina Grande. The measurement scale developed resulted in 7 dimensions and 26 evaluation items, with psychometric consistency of their variables. The relationship between quality dimensions and satisfaction was verified through a forecasting model. The fit of the model revealed that all quality dimensions exert a positive influence on satisfaction, with a higher degree of relative influence of reliability, followed by general safety and comfort. The study contributes to the construction of a measurement scale specific to the service and applicable to the national context. The instrument can be used by local traffic managers to assess the quality of services and promote continuous improvement actions for their users.